Upskilling Older Workers. - Mayhew, K; Elliott, M; Rijkers, B (Oxford Institute of Ageing, 2008)
Governments across much of the developed world are concerned to increase activity rates and employment among older workers and more generally to improve their position in the labour market. The use of education and training provision is prominent among the various policies that have been advocated for this purpose, and this paper evaluates the role that such provision might play. Training is intended to increase the human capital of its recipients by enhancing their knowledge and skills. However, if this training is to improve the labour market position of individuals, the extra human capital must be economically productive and, as with any government intervention, the benefits of the policy must be evaluated against the costs and with alternative policy options in mind.